Emotion regulation strategies in preschool children. (5th July 2014) - Sala, Maria Nives; Pons, Francisco; Molina, Paola
<x xml:space="preserve">Abstract</x> This study investigated the development of emotion regulation strategies as reflected in the narratives of children between the ages of 3 and 6 years. An experimental procedure based on story completion tasks was devised to elicit the emotion‐related narratives of 69 preschool children. Coding of the narratives led to the observation of different emotion regulation strategies: Behavioural strategies, social support, and cognitive reappraisal. Several significant gender and age differences were identified in the use of these strategies. In addition, verbal skills, non‐verbal intelligence, and emotion comprehension were found to be associated with use of the observed emotion regulation strategies, although only at specific ages.